Quest for an Ideal Route of Intubation for Oral and Maxillofacial Surgical Manoeuvres - Vadepally, Ashwant Kumar (J Maxillofac Oral Surg, 2015)
PURPOSE: The optimal route of intubation that may be planned for different oral and maxillofacial surgical manoeuvres. MATERIALS AND METHODS: A study was performed on patients who underwent nasal, oral or submental route of intubation for elective oral and maxillofacial surgery under general anaesthesia. The study variables were the anaesthetic and surgeon factors that should be taken into consideration before intubation and during surgery, and also algorithms for uneventful surgical procedures. The outcome variables were influence of the ‘route of intubation’ on ‘surgical technique’ and vice versa. Overall results were compiled, tabulated and analysed using SPSS version 14.0. RESULTS: The study sample comprised of 634 patients. It was found that 35 % (204) nasal, 7.5 % (4) oral and 0 % submental route of intubation had statistically significant influence on oral and maxillofacial surgical procedures and vice versa (p < 0.001). CONCLUSION: This present study concluded that the surgical access and visibility was immensely improved by following the anaesthetic and surgeon factors in conjunction with algorithms described for uneventful oral and maxillofacial surgical procedures. Further, this has also substantially minimized the influence of the ‘route of intubation’ on ‘surgical technique’ and vice versa.